Humans with obesity exhibit impaired circulating total, but not free, IGF‐1 response to acute endurance exercise - Eduardo D. S. Freitas; Lori R. Roust; Eleanna De Filippis; Matthew Buras; Brooke Brown; Christos S. Katsanos (Physiological Reports)
Abstract We investigated how obesity impacts the response of circulating insulin‐like growth factor‐1 (IGF‐1) to a single bout of endurance exercise in humans with and without obesity. Blood samples were collected before exercise, at 15 and 40 min during a 45‐min cycling session at 65% of heart rate reserve, and 15 min post‐exercise. Serum levels of total IGF‐1, free IGF‐1, IGF binding proteins 1 (IGFBP‐1) and 3 (IGFBP‐3), growth hormone, and insulin were measured. Both total IGF‐1 and IGFBP‐3 serum concentrations increased significantly (p < 0.05) during exercise in the study participants without obesity but not in those with obesity, returning to basal levels immediately after exercise. There was a statistically significant main effect on the growth hormone response, with circulating levels being higher in participants without obesity (p < 0.05). No significant effects were observed for either free IGF‐1 or IGFBP‐1 serum concentrations in response to exercise in either group (p > 0.05). We conclude that humans with obesity have blunted serum total IGF‐1 response during exercise. However, a concurrent attenuation in serum IGFBP‐3 response, which regulates free (i.e., biologically active) IGF‐1 in circulation, results in no change in circulating free IGF‐1 levels during endurance exercise in individuals with obesity.